(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Alternanthera sessils often known as joy weed. It belongs to the family Amaranthaceae; is oneof the most predominant diseased weedsin rice fields of Devarapalli mandal West Godavari district, Andhra Pradesh. The symptoms of this disease appear as reddish pink colorcircular spots on the leaves. The disease severity is maximum in the month of august during kharif season. This study is mainlyconcerned about measurement of disease severity using visual analysis, Image J (IJ), and Leaf doctor (LD) applications. Each diseasedleaf of the plant was exposed to visual assessment, Image J (IJ), and Leaf Doctor (LD) applications. The data was subjected to statisticalanalysis. This study indicates Leaf Doctor (LD) application is accurate, easier, and faster whereas determination of diseased leaf areawith Image J (IJ) application is most suitable.